Effectivity of Information Services in Preventing Bullying at MTs Madinatussalam, Percut Sei Tuan District, Deli Serdang Regency - Abdurrahman, Pratiwi Suci Triadi (International Journal Of Education, Social Studies, And Management (IJESSM), 2021)
This study aims to explore in-depth data about the Effectiveness of Information Services in Bullying Prevention using qualitative research methods with data collection techniques through observation instruments, interviews, and documentation studies. The informants in this study were counseling teachers, the head of a madrasah, and students of MTs Madinatussalam. The results of this study explain that the implementation of information services at MTs Madinatussalam in terms of its implementation is coordinated, systematic, and has been determined through Service Units (Satlan) and Service Implementation Plans (RPL), in preventing bullying by counseling guidance teachers is not only information services. provided but also other services such as group guidance as a follow-up service that aims to achieve self-understanding for victims or students who are potential victims of bullying. Information services in the prevention of bullying at MTs Madinatussalam are already effective and have a good impact on students to create a complete understanding of the benefits of solidarity, mutual respect, and the negative impact of bullying for perpetrators and victims. In this case, it is also assisted by the existence of a special program of the mubaligh corps, mandatory ablution, dhuha prayer, and the participation or coordination of field teachers, homeroom teachers, and counseling guidance personnel in supervising students of MTs Madinatussalam